ESP materials development: Using situation-based vocabulary in composing an English handbook for Customs officers in Northwest region of Vietnam - Trần, Thị Ngọc Mỹ (2020)
The vocabulary has a prominent place in every kind of ESP materials. In ESP, specifically in ESP in Customs field, the learning of specialist vocabulary by the Customs officers has a crucial role in their L2 language utilization. Exposing to newwords is only the first step in learning them. To consolidate them, that is, to ensuretheir transfer to long-term memory, the ESP material users should have ample opportunities to use new words in a variety of situations. The selection of specia list vocabulary in ESP in the way shown in the previous section of this paper seem to contradict what Hutchinson and Waters (1987) say.